2014
DOI: 10.1037/a0035796
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating emotions across contexts: Comparing adults with and without social anxiety disorder using random, social interaction, and daily experience sampling.

Abstract: The ability to recognize and label emotional experiences has been associated with well-being and adaptive functioning. This skill is particularly important in social situations, as emotions provide information about the state of relationships and help guide interpersonal decisions, such as whether to disclose personal information. Given the interpersonal difficulties linked to social anxiety disorder (SAD), deficient negative emotion differentiation may contribute to impairment in this population. We hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
106
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 51 publications
5
106
2
4
Order By: Relevance
“…To increase the generalizability of findings, researchers have tried to understand mental health through noninvasive and real-time data collected from peopleā€™s everyday lives. For example, studies using surveys to repeatedly sample peopleā€™s momentary affective experiences over time have found that individuals with high (vs low) social anxiety symptoms report more anger and fewer and less intense positive emotions [4,5]. While studies that administer repeated surveys offer a glimpse of the socioemotional aspects of daily life, regularly prompting individuals to answer questions also raises the issue of participation burden.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the generalizability of findings, researchers have tried to understand mental health through noninvasive and real-time data collected from peopleā€™s everyday lives. For example, studies using surveys to repeatedly sample peopleā€™s momentary affective experiences over time have found that individuals with high (vs low) social anxiety symptoms report more anger and fewer and less intense positive emotions [4,5]. While studies that administer repeated surveys offer a glimpse of the socioemotional aspects of daily life, regularly prompting individuals to answer questions also raises the issue of participation burden.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with clinical disorders associated with affective problems, such as major depressive disorder (Demiralp et al, 2012), social anxiety disorder (Kashdan & Farmer, 2014), and borderline personality disorder (Suvak et al, 2011) show lower levels of negative emotion differentiation compared to healthy individuals. Also in healthy individuals, the level of emotion differentiation is related to traits such as self-esteem and neuroticism (Erbas, Ceulemans, Pe, Koval, & Kuppens, 2014;Kashdan et al, 2014).…”
Section: An Experience Sampling Study Examining the Potential Impactmentioning
confidence: 99%
“…People's emotion differentiation skill helps transforming negative emotions and stressful experiences, and is an essential component of the emotion regulation process. Research shows that individuals who experience their emotions with more granularity are less likely to resort to maladaptive self-regulatory strategies such as excessive alcohol use (Kashdan, Ferssizidis, Collins, & Muraven, 2010), aggression (Pond Jr et al, 2012), self-injurious behavior (Zaki, Coifman, Rafaeli, Berenson, & Downey, 2013), and they show less neural reactivity to rejection (Kashdan et al, 2014). Despite its central role in mental well-being, there is few, if any, research, that has been able to identify factors that may change an individual's level of emotion differentiation.…”
Section: An Experience Sampling Study Examining the Potential Impactmentioning
confidence: 99%
“…For instance, individuals with depression demonstrate poor understanding of their emotions and are less accepting of their emotions than those without depression (Ehring, Tuschen-Caffier, SchnĆ¼lle, Fischer, & Gross, 2010; Mennin, Holaway, Fresco, Moore, & Heimberg, 2007). Similarly, socially anxious individuals are characterized by difficulty identifying their emotions, describing their emotions, and differentiating between different types of emotion (Kashdan & Farmer, 2014; Mennin et al, 2007; Spokas, Luterek, & Heimberg, 2009; Turk, Heimberg, Luterek, Mennin, & Fresco, 2005). Thus, emotional difficulties may underlie both depression and social anxiety.…”
mentioning
confidence: 99%